Phenotypic and behavioral variability within Angelman Syndrome group with UPD - Fridman,Cintia (2002)
The Angelman syndrome (AS) (developmental delay, mental retardation, speech impairment, ataxia, outbursts of laughter, seizures) can result either from a 15q11-q13 deletion, or from paternal uniparental disomy (UPD), imprinting, or UBE3A mutations. We describe here the phenotypic and behavioral variability detected in eight UPD patients out of a group of 58 AS patients studied. All of them presented developmental delay, mental retardation, ataxia, speech impairment, and frequent drooling. Only one had microcephaly, whereas in two of them the OFC (head circumference) was above the 98th percentile. The weight of all patients was above the 50th percentile, and in three of them the height was above the 90th percentile. Three were able to say a few words and to communicate by gestures. Two patients presented hyperphagia, and three presented skin picking, common features in the Prader-Willi syndrome (PWS). Four patients (4/7) had wide-spaced teeth. Five presented seizures, and two others did not manifest frequent laughter. One patient was very different from the others, as he showed a better understanding and abilities to communicate, to play video games and to draw. We suggest here that there seems to be an extreme phenotypic and behavioral variability within the UPD group, and that both typical patients and those with mental retardation, language impairment, happy disposition, and hyperactivity should be tested for AS.